Separation of nadolol racemates by high pH reversed-phase preparative chromatography - Arafah, Rami (2018)
The separation of nadolol racemates under high pH reversed-phase preparative chromatography is presented for the first time. Three Waters C18 adsorbents (XBridge, Shield and XSelect) are compared for the separation of nadolol racemates using ethanol:water:diethylamine solvent mixtures. Experimental and simulation results are presented to compare the separation performances at preparative scale using both the fixed-bed and the simulated moving bed operations. The Waters XBridge C18 adsorbent and an ethanol:water:diethylamine solvent mixture are selected as a good option for the separation of nadolol racemates. The validated methodology allows the separation of a multicomponent nadolol feed mixture composed by four stereoisomers into two pure racemates (two pairs of enantiomers). This work introduces the potential of using an initial achiral separation step in the global strategy for the complete multicomponent separation of the four nadolol stereoisomers.